Pengaruh Ekstrak Daun Nerium oleander L. terhadap Mortalitas dan Perkembangan Hama Spodoptera litura Fab. - Heri Prabowo (Universitas Atma Jaya Yogyakarta, 2010)
Research was conducted at the Laboratory of Entomology, Tobacco and Fiber Crops Research Center from June to July 2009. Tests were conducted on the larvae of Spodoptera litura second instar. Concentration of leaf extract of N. oleander used was 0; 2x105; 3x105; 4x105; and 5x105ppm. Treatment was done by spraying method in the spray chamber. Treatment was arranged in a completely randomized design (RAL) with 4-time repetition. Each repetition used 25 larvae. Observed parameters included the death for every 24, 48, 72, and 96 hours; length, width, and weight of larvae after 96 hours after treatment. By 96 hours after treatment with the concentration of leaf extract 0; 2x105; 3x105; 4x105; and 5x105ppm it was capable of causing mortality S. litura, respectively for 0; 48.33; 53.33; 66.67%, dan 76.67%. By 96 hours after treatment extract concentration required to cause mortality S. litura was 25, 50, and 95% respectively of 2.35x105, 4.44x105, and 9.49x105ppm. After 96-hour treatment the concentration of leaf extract 0; 2x105; 3x105; 4x105; and 5x105ppm could cause the length, width, and weight of S. litura, respectively for 0.89 mm; 0.91 mm; 0.93 mm; 0.94 mm; 0.95 mm; 0.15 mm; 0.16 mm; 0.17 mm; 0.18 mm; 0.19 mm, 0.011 g; 0.012 gr; 0.013 g; 0.014 g and 0.016 gr. The use of N. oleander leaf extract caused mortality of S. litura between 13.33−76.67% at 24 to 96 hours after treatment. Leaf extract of N. oleander potentially caused mortality S. litura. The use of this leaf extract could also inhibit the length, width, and weight of larvae.